2016
DOI: 10.1016/j.nicl.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

High-density electroencephalographic recordings during sleep in children with disorders of consciousness

Abstract: IntroductionA large number of studies have investigated neural correlates of consciousness in adults. However, knowledge about brain function in children with disorders of consciousness (DOC) is very limited. We suggest that EEG recordings during sleep are a promising approach. In healthy adults as well as in children, it has been shown that the activity of sleep slow waves (EEG spectral power 1–4.5 Hz), the primary characteristic of deep sleep, is dependent on use during previous wakefulness. Thus the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
(57 reference statements)
1
33
0
Order By: Relevance
“…DOC patients do not show systematic variance of sleep spindles and slow-wave oscillations between day and night [ 55 ]. Moreover, a reduction in the build-up of slow-wave oscillations during sleep over parietal brain areas is commonly found in DOC patients, which is considered a characteristic topographical marker for network dysfunction [ 56 ].…”
Section: Spontaneous Electroencephalogrammentioning
confidence: 99%
“…DOC patients do not show systematic variance of sleep spindles and slow-wave oscillations between day and night [ 55 ]. Moreover, a reduction in the build-up of slow-wave oscillations during sleep over parietal brain areas is commonly found in DOC patients, which is considered a characteristic topographical marker for network dysfunction [ 56 ].…”
Section: Spontaneous Electroencephalogrammentioning
confidence: 99%
“…21) during sleep are considered a reliable marker of sleep need and have been linked to brain plasticity that occurs during brain maturation, learning, but also in response to brain injuries. 20,22,23 Another characteristic feature of physiological sleep architecture is its periodicity. In healthy individuals the alternation between deep and lighter sleep is observed over the night with 4-6 full cycles.…”
Section: The Aim Of This Studymentioning
confidence: 99%
“…In a recent survey conducted among the E-PILEPSY reference centres in Europe it was reported that seven centres apply MEG source localization, and nine centres apply EEG source localization. Fourteen centres use combinations of inverse methods and head models [32].…”
Section: Current Role Of Meg In Pre Surgical Evaluationmentioning
confidence: 99%